Of the Contract - Clifton, Christopher (punctum books, 2017)
Of the Contract is a version of a text that is as old as any memory, or a form of legal instrument that constitutes the basis of the world in which its terms have been translated. The text remains as open to renewal as that world remains to future alteration, and the terms are both already past, and always yet to come. The notion of the debt that is presented by the contract corresponds to a conception of accountancy and finance that provide a new approach to the contemporary problem of the sense of that external to the terms of human access. A reinterpretation of the philosophical tradition that runs through Levinas and Heidegger to Kant, Of the Contract is also grounded in the medieval tradition that was centered on the notion of "contraction," and its writing was inspired by forms of life such as those found in the development of monastic constitutions, and the novels of knight errantry. It is also an oblique contribution to the recent discussions on the nature of debt, and is deeply marked by an awareness of climate change, and the insufficiencies of capital to overcome this crisis. All of these concerns however were contracted in a more acute awareness of the process of expression, and the work is given first of all as literature. It is the nature of the terms that they are open to untold interpretations.